Effects of EPA and Vitamin E on Serum Enzymatic Antioxidants and Peroxidation Indices in Patients with Type II Diabetes Mellitus - SH Sarbolouki; M Djalali; AR Dorosty; MR Eshraghian; SAR Ebadi; SB Hashemi; SB Hashemi (Tehran University of Medical Sciences, 2010)
Background: Diabetes mellitus is associated with chronic changes in peripheral arteries because of oxidative stress and insufficient antioxidative defense mechanism. Omega-3 fatty acid supplementation could be effective in some diabetes complications; however, polyunsaturated fatty acids may increase lipid peroxidation. This study aimed to determine whether eicosapentaenoic acid alone or in conjunction with vitamin E had differential effects on serum antioxidants and peroxidation indices. Methods: This double-blind, placebo-controlled trial was carried out on 136 patients with type II diabetic mellitus (age 48.8±4.4 yr, BMI 27.8±1.7 kg/m²). The four groups of the study either received two grams of omega-3 fatty acids, 400 IU of vitamin E, a combination of the two or placebo for three months. Their serum total antioxidant capacity, enzymatic antioxidants and peroxidation indices were assessed. Result: Fasting serum TAC increased in EPA+E (10.7%, P< 0.001) and E groups (7.5%, P< 0.05). SOD, G-PX and G-RD increased in EPA group (7.3%, 5.1%, and 8.4%, P< 0.05, respectively). MDA and protein carbonyl decreased in EPA and E groups (respectively, 12.5%, 7.6% P< 0.05, P< 0.05; 13%, 15.3% P< 0.001, P< 0.05). After adjustment for baseline values, age, sex, BMI and duration of diagnosed diabetes, protein carbonyl decreased in EPA+E and E group (30.7%, 15.3%; P< 0.05 respectively) relative to the placebo group. Conclusion: EPA, by itself has a statistically significant effect on serum total antioxidant capacity, enzymatic antioxidants and peroxidation indices in diabetic patients compared to EPA+E or E alone. Trial registration: ClinicalTrials.gov NCT00817622